Unbiased Analysis Method for Measurement of Red Blood Cell Size and Velocity With Laser Scanning Microscopy - Chaigneau, Emmanuelle; Roche, Morgane; Charpak, Serge (Frontiers in Neuroscience, 2019)
Two-photon laser scanning microscopy is widely used to measure blood hemodynamics in brain blood vessels. Still, the algorithms used so far to extract red blood cell (RBC) size and velocity from line-scan acquisitions have ignored the extent to which scanning speed influences the measurements. Here, we used a theoretical approach that takes into account the velocity and direction of both scanning mirrors and RBCs during acquisition to provide an algorithm that measures the real RBC size and velocity. We validate our approach in brain vessels of anesthetized mice, and demonstrate that it corrects online measurement errors that can reach several tens of percent as well as data previously acquired. To conclude, our analysis allows unbiased comparisons of blood hemodynamic parameters from brain capillaries and large vessels in control and pathological animal models.